Authigenic Greigite as an Indicator of Methane Diffusion in Gas Hydrate-Bearing Sediments of the Hikurangi Margin, New Zealand - Kars, Myriam; Greve, Annika; Zerbst, Lilly (Frontiers in Earth Science, 2021)
Authigenic ferrimagnetic iron sulfides, essentially greigite (Fe3S4), are commonly found in gas hydrate-bearing marine sediments of active accretionary prisms. Greigite is a by-product, either intracellular or extracellular, of microbial activity, and therefore provides good indication of microbial processes which are closely related to the occurrence of gas hydrate. A high-resolution rock magnetic study was conducted at Site U1518 of International Ocean Discovery Program Expedition 375, located in the frontal accretionary wedge of the Hikurangi Margin, offshore New Zealand. Samples were collected throughout the entire recovered stratigraphic sequence, from the surface to ~492 meters below seafloor (mbsf) which includes the Pāpaku fault zone. This study aims to document the rock magnetic properties and the composition of the magnetic mineral assemblage at Site U1518. Based on downhole magnetic coercivity variations, the studied interval is divided into five consecutive zones. Most of the samples have high remanent coercivity (above 50 mT) and first-order reversal curves (FORC) diagrams typical of single-domain greigite. The top of the hanging wall has intervals that display a lower remanent coercivity, similar to lower coercivities measured on samples from the fault zone and footwall. The widespread distribution of greigite at Site U1518 is linked to methane diffusion and methane hydrate which is mainly disseminated within sediments. In three footwall gas hydrate-bearing intervals, investigated at higher resolution, an improved magnetic signal, especially a stronger FORC signature, is likely related to enhanced microbial activity which favors the formation and preservation of greigite. Our findings at the Hikurangi Margin show a close linkage between greigite, methane hydrate and microbial activity.